2022
DOI: 10.3389/fpsyg.2022.826476
|View full text |Cite
|
Sign up to set email alerts
|

Motor Imagery and Action Observation as Appropriate Strategies for Home-Based Rehabilitation: A Mini-Review Focusing on Improving Physical Function in Orthopedic Patients

Abstract: Dynamic stability of the knee and weakness of the extensor muscles are considered to be the most important functional limitations after anterior cruciate ligament (ACL) injury, probably due to changes at the central (cortical and corticospinal) level of motor control rather than at the peripheral level. Despite general technological advances, fewer contraindicative surgical procedures, and extensive postoperative rehabilitation, up to 65% of patients fail to return to their preinjury level of sports, and only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 93 publications
(162 reference statements)
0
6
0
Order By: Relevance
“…Considering MI practice programming, only one review with meta-analysis examined a MI practice dose-response relationship, suggesting that effects of cognitive training on outcomes in TKA patients were predicted by the total number of training sessions per study [9]. A recent review by Paravlic suggested recommendations for MI rehabilitation practice in the home setting [32]. In brief, there are some steps that should be followed to benefit from MI practice: (a) patients' imagery ability must be assessed to inform the therapist which MI perspective and which MI type should be used; (b) it is recommended to provide patients with audio instructions to follow during practice sessions [33]; (c) at the beginning of MI practice therapist should propose simple motor task that is easy to perform by patient and (d) the following motor imagery variables were associated with strength improvement: a training period of 4 weeks, a training frequency of three sessions per week, a training volume of two to three sets, 25 repetitions per set and a single session duration of 15 minutes [19].…”
Section: Discussionmentioning
confidence: 99%
“…Considering MI practice programming, only one review with meta-analysis examined a MI practice dose-response relationship, suggesting that effects of cognitive training on outcomes in TKA patients were predicted by the total number of training sessions per study [9]. A recent review by Paravlic suggested recommendations for MI rehabilitation practice in the home setting [32]. In brief, there are some steps that should be followed to benefit from MI practice: (a) patients' imagery ability must be assessed to inform the therapist which MI perspective and which MI type should be used; (b) it is recommended to provide patients with audio instructions to follow during practice sessions [33]; (c) at the beginning of MI practice therapist should propose simple motor task that is easy to perform by patient and (d) the following motor imagery variables were associated with strength improvement: a training period of 4 weeks, a training frequency of three sessions per week, a training volume of two to three sets, 25 repetitions per set and a single session duration of 15 minutes [19].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike AOT, motor imagery is a mental simulation of a specific muscle action without any corresponding motor output. These motor simulation practice techniques have been proven to enhance recovery and muscle strength during the injury rehabilitation period (Paravlic, 2022).  Local vibration increases muscle activity and, therefore, has been used for rehabilitation and performance enhancement.…”
Section: Practical Recommendationsmentioning
confidence: 99%
“…It is possible to acquire novel motor skills or to improve motor performance by observing the actions of others (Mattar and Gribble, 2005;Osman et al, 2005;Porro et al, 2007;Lee et al, 2013;Kim et al, 2017). Action observation (AO) has been found to improve a variety of motor tasks, such as serial reaction time tests (Osman et al, 2005) and force production (Porro et al, 2007), among healthy subjects and populations with neurological (Pelosin et al, 2010(Pelosin et al, , 2013Buccino et al, 2011;Lee et al, 2013;Park and Hwangbo, 2015) and orthopedic conditions (Paravlic, 2022) (however, see also Sarasso et al, 2015;Gatti et al, 2019;Borges et al, 2022).…”
Section: Introductionmentioning
confidence: 99%